Protecting emotional wellbeing during childbirth: exploring the role of organisational regulatory processes in promoting compassion - Redhead, Caroline A. B. (Frontiers in Global Women's Health, 2025)
In this article I consider how legal processes have power to facilitate or impede emotional safety and wellbeing for women and birthing people. I suggest that the use of therapeutic jurisprudence to re-view NHS Foundation Trusts’ organisational and regulatory processes can offer new insights. Therapeutic jurisprudence is an approach which pays purposeful attention to the therapeutic (or harmful) consequences of legal processes and how they impact the psychological well-being of those upon whom they act. The report of the Inquiry into maternity and neonatal services at East Kent Hospitals University NHS Foundation Trust was the catalyst for the theoretical suggestions I make in this article. In its response to this report, the Government has acknowledged the importance of a culture of honesty, compassion and safety. However, none of the Government's recommendations considers the impact of organisational regulatory processes on the provision of compassionate care. My argument here is that such processes are neither inert nor benign. Critical socio-legal literature provides clear evidence of the anti-therapeutic potential of hierarchical organisational structures, and this is confirmed by the findings of the East Kent Report. Presenting a brief, therapeutic jurisprudence-informed review of some of the findings of the East Kent report, I suggest that a re-view of NHS Trusts’ constitution and governance processes might offer the new means of tackling maternity service failures for which Bill Kirkup called in the East Kent Report, with the ultimate aim of ensuring emotional safety and wellbeing for pregnant and birthing people in childbirth.